Transforming Nepal’s primary health care delivery system in global health era: addressing historical and current implementation challenges - Bipin Adhikari; Shiva Raj Mishra; Ryan Schwarz (Globalization and Health, 2022)
Abstract Nepal’s Primary Health Care (PHC) is aligned vertically with disease control programs at the core and a vast network of community health workers at the periphery. Aligning with the globalization of health and the factors affecting global burden of diseases, Nepal echoes the progressive increase in life expectancy, changes in diseases patterns, including the current impact of COVID-19. Nepal’s health system is also accommodating recent federalization, and thus it is critical to explore how the primary health care system is grappling the challenges amidst these changes. In this review, we conducted a narrative synthesis of literature to explore the challenges related to transformation of Nepal’s primary health care delivery system to meet the demands incurred by impact of globalization and recent federalization, covering following database: PubMED, Embase and Google Scholar. Of the 49 articles abstracted for full text review, 37 were included in the analyses. Existing theories were used for constructing the conceptual framework to explain the study findings. The results are divided into four themes. Additional searches were conducted to further support the narrative synthesis: a total of 46 articles were further included in the articulation of main findings. Transforming Nepal’s primary health care system requires a clear focus on following priority areas that include i) Revised efforts towards strengthening of community based primary health care units; ii) Adapting vertical programs to federal governance; iii) Reinforcing the health insurance scheme; and iv) Strengthening an existing network of community health workers and health human resources. This review discusses how these broad goals bear challenges and opportunities.